Development of a Modular, Induced Fluorescence-based Instrument Family – The Aquafluosense Project - Székács, András (Journal of Central European Green Innovation, 2022)
In the scope of our recently completed AQUAFLUOSENSE research and development project, the design and construction of a prototype of an electron excitation fluorescence-based analytical instrument family has been carried out for water quality measurement applications. The objective of the project was to develop a new water analysis system for natural and artificial waters, allowing complex, systematic and for main parameters in situ assessment and monitoring of water quality, by developing a modular instrument family that can be individually configured for target tasks at each monitoring point. Within the instrument family, created in a collaboration of working groups of a number of research and development institutions, different modules allow for the determination of key water parameters. A common optical characteristic of these modules is that they measure the target parameter on the basis of an induced (excitation) fluorescence signal generated in the test sample. The modules allow the determination of individual biological or chemical components based either on measuring their fluorescence directly (direct fluorescence) or by relying on detection of the fluorescence of a coupled dye (indirect fluorescence). Thus, the instrument modules provide experimental data on the algal density and the total organic carbon content, as well as the presence of certain organic micropollutants in the given water body studied, the latter target analytes detected by direct fluorescence measurement or by an immunofluorescence measurement modality.